Post-pandemic transformations: How and why COVID-19 requires us to rethink development - Leach, Melissa; MacGregor, Hayley; Scoones, Ian; Wilkinson, Annie (World development, 2021)
•COVID-19 has exposed major faultlines and fragilities in current systems.•A structural-unruly duality characterises emergence, progression and impact.•Mainstream development thinking and practice are part of the problem.•Transformations are needed in science-policy, economies and governance.•Resilience, equity, diversity, care and inclusive politics are required. COVID-19 is proving to be the long awaited ‘big one’: a pandemic capable of bringing societies and economies to their knees. There is an urgent need to examine how COVID-19 – as a health and development crisis - unfolded the way it did it and to consider possibilities for post-pandemic transformations and for rethinking development more broadly. Drawing on over a decade of research on epidemics, we argue that the origins, unfolding and effects of the COVID-19 pandemic require analysis that addresses both structural political-economic conditions alongside far less ordered, ‘unruly’ processes reflecting complexity, uncertainty, contingency and context-specificity. This structural-unruly duality in the conditions and processes of pandemic emergence, progression and impact provides a lens to view three key challenge areas. The first is how scientific advice and evidence are used in policy, when conditions are rigidly ‘locked in’ to established power relations and yet so uncertain. Second is how economies function, with the COVID-19 crisis having revealed the limits of a conventional model of economic growth. The third concerns how new forms of politics can become the basis of reshaped citizen-state relations in confronting a pandemic, such as those around mutual solidarity and care. COVID-19 demonstrates that we face an uncertain future, where anticipation of and resilience to major shocks must become the core problematic of development studies and practice. Where mainstream approaches to development have been top down, rigid and orientated towards narrowly-defined economic goals, post-COVID-19 development must have a radically transformative, egalitarian and inclusive knowledge and politics at its core.